A universal single electrode droplet-based electricity generator (SE-DEG) for water kinetic energy harvesting. (April 2021) - Zhang, Nan; Gu, Haojie; Lu, Keyu; Ye, Shimeng; Xu, Wanghuai; Zheng, Huanxi; Song, Yuxin; Liu, Chaoran; Jiao, Jiwei; Wang, Zuankai; Zhou, Xiaofeng
Abstract: Harvesting water kinetic energy is a prospective way to obtain sustainable power. However, conventional water energy harvesting technologies are restricted by specific operating locations and fabrication materials. These techniques urgently need to be improved and supplemented with new methods. Here, we report a novel and universal single electrode droplet-based electricity generator (SE-DEG) that allows converting water droplet kinetic energy into electricity power on any surfaces of artificial or natural materials such as PTFE, glass, wood, aloe, cicada wing, stone and etc. This functionality is endowed by a special configuration characterized by the location of the electrode on the top of dielectric material rather than underlying as in the conventional triboelectric nanogenerator (TENG). Such special configuration can effectively harness the triboelectric charges generated without going through the electrostatic induction process between bottom electrode and the surface in the case of TENG. We envision that SE-DEGs represent a new dimension in ability to harvest abundant hydrodynamic energy everywhere. Graphical Abstract: ga1 Highlights: A universal SE-DEG represents a new dimension in ability to harvest abundant hydrodynamic energy everywhere. The universal preparation makes the operating locations and fabrication materials of the generator unrestricted. The design of the electrode can harness the triboelectric charges without going through electrostatic induction process.